Nigeria-India Bilateral Trade Relations: An Analysis of Trade Complementarity Index (TCI) - Ibrahim, Kabiru Hannafi; Shehu, Abdulaziz (Asian Journal of Economic Modelling, 2016)
This study used simple descriptive analysis and trade complementarity index to examine Nigeria-India bilateral trade relations for the period 2000-2014. Evidence from the trade composition result shows that Nigeria’s imports from India are more diversified than its exports. All the major products imported from India by Nigeria accounts for a very much significant share in its total imports while for the exports only mineral fuels seem to contribute much to the Nigeria’s exports to India. Throughout the whole period, there exist a partial match between Nigeria’s exports supply and the India’s imports demand as the trade complementarity indices lies between 31.98 and 45.21. Despite the existence of partial export and import match between Nigeria and India the trade complementarity index has been steadily increasing from 2000-2014, implying that Nigeria and India trade profiles are becoming more compatible. Thus, the study also recommends that the Nigerian government, export promotion agencies, ministries, exporters and other stakeholders should focus attention on identify realistic export opportunities in Indian markets in order to boost and diversified Nigeria’s export through the use of more scientific, realistic and empirical approach.